Endometriosis. Pathological Anatomy. - Takano Morón, Juan (2015)
Endometriosis occurs with many morphological patterns because, unlike adenomyosis, almost invariably suffer influence ovarian hormonal changes. In the ovary is presented as small cortical nodulitos reddish dark blue, particularly at the free edge and the side surfaces, remembering foci of fibrin deposits.